Caracteres epidemiológicos e uso da análise de agrupamento para resistência parcial à ferrugem da soja - Martins, Juliana Araújo Santos (2006)
This study evaluated the reaction of 68 soybean genotypes for partial resistance against Phakopsora pachyrhizi. The experiment was done in Uberlândia-MG, in a greenhouse, from December 2004 to February 2005, consisting of three evaluation times. The following resistance characteristics were evaluated: average latent period (ALP), average number of pustules per leaflet and rust severity. The area under the disease progress curve (AUDPC) was calculated based on the variables average number of leaflet pustules and severity. Analysis of variance and comparison of the averages by the Scott Knott test were done at 5% probability. Significant differences were found among the genotypes for the average number of leaflet pustules and rust severity twelve days after inoculation. Differences were also found for the area under the disease progress curve. It is assumed that partial resistance to soybean Asian rust should be evaluated under average epidemics conditions. This evaluation was done on the second time with all characters evaluated. Three genotypes (number 4, 41, and 42), referring to parents Cristalina and IAC 100, presented greater partial resistance to soybean rust. Genotype grouping, by cluster multivariate analysis and principal components analysis allowed the discrimination of partially resistant genotypes.